KINERJA PERUSAHAAN UD LIMAS MERTHA MANDIRI DI DESA KEROBOKAN, KECAMATAN KUTA UTARA, KABUPATEN BADUNG BERDASARKAN PENDEKATAN BALANCED SCORECARD - Anak Agung Wulandari; I Made Antara; Ketut Suamba (Universitas Udayana, 2019)
Assessing or measuring performance is one of the key factors for the company. Guaranteed company performance runs smoothly, and it is necessary to evaluate the company performance. This study aims to measure the performance of UD Limas Mertha Mandiri (UD. LMM) through the Balanced Scorecard approach. UD. LMM is a company engaged in the field of staple food (agricultural products). The research method used was the sample census method with a total of 38 respondents, including 18 employees and 20 regular customers. In conducting assessments, appropriate performance measurements are needed, not only for the financial sector but also for the non-financial sector. Position is calculated using the Balanced Scorecard method. The results show that: (1) The view of finance is considered quite good because it is measured using five ratios, namely liquidity ratios, profitability, solvency ratios, leverage ratios and activity ratios. (2) The customer's point of view is a good standard because it meets customer expectations. (3) The internal business process perspective is considered good because the time to process the order transaction is valid. (4) The learning and growth perspective is in a good standard because employee productivity increases and net income increases. The advice that can be given to the next researcher is to improve the company's performance using SWOT, which makes the company's performance more measurable.